CONTENT OF SEQUENTIAL FORMATION OF HUMANITIES TEACHERS’ PEDAGOGICAL REFLECTION IN POSTGRADUATE EDUCATION - Ковтун, O.; Сенчина, H. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The article is dedicated to the problem of formation of humanities teachers’ pedagogical reflection in postgraduate education. Pedagogical reflection of humanities teachers is defined as an integral characteristic of the personality, as a mechanism of professional self-improvement and self-actualization, which manifests itself in the ability of the teacher to take analytical position toward his/her professional activity and him/herself as its subject, considering the developing potential of the humanities. Reflection is an ability that can be shaped and developed, and the most effectively this is achieved in conditions of specially organized activity, in particular in postgraduate education. Experimental methods of humanities teachers’ pedagogical reflection in postgraduate education (cognitive-motivational, integrative-practical, creative-professional stages) were developed and tested. The experimental educational process was preceded by a propaedeutic stage aimed at updating content of postgraduate pedagogical education from the standpoint of a reflexive paradigm, providing an integrative approach to the educational process, developing educational and methodological support for the educational process to ensure the formation of pedagogical reflection, conducting a methodological seminar with teachers who were involved in the experiment. The first – cognitive-motivational – stage was aimed at providing positive motivation of humanities teachers for the formation of pedagogical reflection in postgraduate education; providing teachers with knowledge about the concept "pedagogical reflection", familiarizing them with methods of diagnosis and development of pedagogical reflection. The second – integrative and practical – stage was aimed at attracting teachers to active professionally-oriented reflexive activity, carried out on the basis of the integrative course "Reflective Practice for Teachers of the Humanities", aimed at the formation of reflexive skills. The aim of the third – creative-professional – stage was to immerse teachers into active reflexive professional activity during the period of pedagogical practice and in the intercourse period in postgraduate education; stimulate creative application of the formed reflexive skills. Methods and means of training: reflexive-oriented problem lectures, reflexive disputes, reflexive exercises and games, individual and group reflection, reflexive analysis of pedagogical situations, pedagogical practice, reflexive analysis of teacher’s activity at the lesson, self-analysis, self-assessment and mutual evaluation; setting at self-development and self-realization